INVITRO TOXICITY OF SILVER NANOPARTICLES SYNTHESIZED BY USING CLOVES OF SYZYGIUM AROMATICUM AGAINST HEp-2 CELLS DERIVED FROM LARYNX CARCINOMA - VENUGOPAL KRISHNAN,; RAJAGOPAL KALYANARAMAN, (International Journal of Pharma and Bio Sciences, 2016)
Present study reports sucessfull bio-synthesis of silver nanoparticles (AgNPs) using aqueous extract of cloves (Syzygium aromaticum) belonging to family Myrtaceae. The obtained nanoparticles were characterized by using UV–vis spectroscopy and transmission electron microscopy (TEM) and HR-TEM. The AgNPs were spherical, poly-dispersed and well scattered with a size ranging from 10 to 80 nm. The FTIR results confirmed the role of protiens liable for silver nitrate reduction into AgNPs. The biosynthesized silver nanoparticles were checked for their cytotoxic property against HEp-2 cell line derived from larynx carcinoma. The results of MTT measures of AgNPs analyzed at different concentrations extending from 10 to 100μg/ml, demonstrated a considerable dose dependent toxicity of silver nanoparticles for HEp-2 cell line. The outstanding morphology appropriately relevant for anticancer property of silver nanoparticles against HEp-2 cells will have a beneficial impact of utilizing biosynthesized nanoparticles for cancer therapy.